Clinical and Functional Outcomes of Lens-Iris Diaphragm Implantation with Simultaneous Subtotal Penetrating Keratoplasty: a 15-Year Follow-Up Case Report - Yu. Yu. Kalinnikov; N. P. Sobolev; S. V. Novikov; A. V. Zinov’eva; D. V. Nevrov (Oftalʹmologiâ, 2019)
Combined traumatic injuries of the anterior eye segment are attributed to the severe consequences of the injured organ of vision. Iris defects result in spherical and chromatic aberrations, diplopia, flares, severe photophobia, cosmetic defects, and significantly reduced visual acuity after the injury. The literature describes various methods to restore visual functions impaired as a result of aniridia. Use of an artificial iris together with an intraocular lens pathology results in optimal reconstruction and recovery of normal anterior segment anatomy and topography. In this paper, we provide a report on a patient followed up for 15 years after combined reconstruction eye surgery for an off-the-job penetrating eye injury sustained in 2003. A complex intervention was required due to the involvement of the cornea, iris, and lens. In 2004, the patient underwent a lens-iris diaphragm implantation combined with penetrating keratoplasty. The diaphragm implantation was followed by an improvement in visual acuity and elimination of photophobia and flares. There were no intra- or postoperative complications. Two years later, LASIK refractive surgery was performed on the corneal transplant to eliminate induced ametropia. The patient retained good eye function, with a stable position of the lens-iris diaphragm, for many years after the diaphragm implantation, keratoplasty, and refractive surgery. In 2018, he had an intravitreal implant impregnated with dexamethasone, as changes in the retina had developed. The long-term follow-up in this case demonstrates that the implantation of a lens-iris diaphragm resulted in an elimination of undesirable optical events associated with aniridia and produced an optimal functional result, while also improving the patient’s quality of life with a good aesthetic effect.